2018
DOI: 10.1038/s41598-018-34930-6
|View full text |Cite
|
Sign up to set email alerts
|

Combinational Biomarkers for Atrial Fibrillation Derived from Atrial Appendage and Plasma Metabolomics Analysis

Abstract: Atrial fibrillation (AF) is one of the most common types of arrhythmias and often leads to clinical complications. The objectives of this study were to offer insights into the metabolites of AF and to determine biomarkers for AF diagnosis or prediction. Sixty atrial appendage samples (AF group: 30; non-AF group: 30) and 163 plasma samples (AF group: 48; non-AF group: 115) from 49 AF patients and 116 non-AF patients were subjected to liquid chromatography positive ion electrospray ionization tandem mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…The PREDIMED cohort reported positive associations between plasma choline and increased risk of major cardiovascular events [74]. In a recent cross-sectional study of 49 atrial fibrillation (AF) patients, plasma choline concentrations were higher than normal [75]. Results from 3 prospective cohort studies are also consistent with respect to the association between plasma choline and AF incidence [76].…”
Section: Where Does Tmao Come From?mentioning
confidence: 87%
“…The PREDIMED cohort reported positive associations between plasma choline and increased risk of major cardiovascular events [74]. In a recent cross-sectional study of 49 atrial fibrillation (AF) patients, plasma choline concentrations were higher than normal [75]. Results from 3 prospective cohort studies are also consistent with respect to the association between plasma choline and AF incidence [76].…”
Section: Where Does Tmao Come From?mentioning
confidence: 87%
“…There have been a few small-scale studies comparing the metabolomics profile of patients with prevalent AF with that of controls without AF. 27,28 However, because patients with AF most often receive medications with possible effects on the metabolome, such studies are hard to interpret.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“… 45 Glutamate was also found to be significantly increased in AF patient left atrial appendages. 46 Glutamate signaling is important in vagal afferent neurons, 47 and remodeling of the glutamate system in AF may relate to the extensive previous evidence of autonomic dysfunction in patients with AF. 48 Moreover, a recent study has shown fundamental roles for glutamatergic receptors in rat atrial cardiomyocytes and induced pluripotent stem cell-derived atrial cardiomyocytes, including a reduction in cardiomyocyte excitability after GRIA3 knockdown.…”
Section: Discussionmentioning
confidence: 99%